An Analysis of Mandatory Auditor Rotation Requirements in South Africa in light of International Legislative Trends - Vela Madlela (Obiter, 2019)
An independent and objective external audit of companies is an integral element of sound corporate governance and of functional financial markets. The issues relating to auditor independence and objectivity have attracted considerable regulatory and public scrutiny in many leading jurisdictions. This is partly due to a general decrease in audit quality over the years as evidenced by high-profile accounting scandals and audit failures, both locally and internationally, as well as the vital role that an external audit is expected to play in ensuring transparency, accuracy and efficiency in the financial markets. In an attempt to restore confidence in the audit profession and to strengthen the independence of the external audit function for companies, legislatures in some leading jurisdictions have introduced a variety of regulatory strategies, including mandatory rotation of auditors in the form of mandatory audit partner rotation (MAPR) and/or mandatory audit firm rotation (MAFR). In this article, the author examines the adequacy of the current provisions of section 92 of the Companies Act 71 of 2008 regarding MAPR and the recently promulgated rule of the Independent Regulatory Board for Auditors (IRBA) on MAFR (the MAFR rule) in addressing the issue of mandatory auditor rotation in South Africa. The author considers whether the provisions of the Companies Act 71 of 2008 regarding MAPR and the MAFR rule are adequate to promote an independent and objective external audit function for companies, as well as transparency, efficiency and accountability, while providing certainty for companies and auditors. The author first examines some of the key principles and policy considerations relating to the external audit of companies – namely, the significance of audits and auditors in the financial markets as well as the value of auditor independence and objectivity. This is followed by an examination of the provisions of section 92 of the Companies Act 71 of 2008 regarding MAPR and the recently promulgated MAFR rule in light of legislative developments in the United States, Canada, the European Union, Australia and India regarding mandatory rotation of auditors and audit partners. Based on the lessons to be drawn from the experiences of the above jurisdictions, the author then makes recommendations for appropriate reforms for South Africa in this important area of company law. This is followed by some concluding remarks.